Increased circulating pro-brain natriuretic peptide (proBNP) and brain natriuretic peptide (BNP) in patients with cirrhosis: relation to cardiovascular dysfunction and severity of disease. Issue 10 (11th September 2003) - Henriksen, J H; Gøtze, J P; Fuglsang, S; Christensen, E; Bendtsen, F; Møller, S
Abstract : Background and aims: Cardiac dysfunction may be present in patients with cirrhosis. This study was undertaken to relate plasma concentrations of cardiac peptides reflecting early ventricular dysfunction (pro-brain natriuretic peptide (proBNP) and brain natriuretic peptide (BNP)) to markers of severity of liver disease, cardiac dysfunction, and hyperdynamic circulation in patients with cirrhosis. Patients and methods: Circulating levels of proBNP and BNP were determined in 51 cirrhotic patients during a haemodynamic investigation. Results: Plasma proBNP and BNP were significantly increased in cirrhotic patients (19 and 12 pmol/l, respectively) compared with age matched controls (14 and 6 pmol/l; p<0.02) and healthy subjects (<15 and <5.3 pmol/l; p<0.002). Circulating proBNP and BNP were closely correlated ( r = 0.89, p<0.001), and the concentration ratio proBNP/BNP was similar to that of control subjects (1.8 v 2.3; NS). Circulating proBNP and BNP were related to severity of liver disease (Child score, serum albumin, coagulation factors 2, 7, and 10, and hepatic venous pressure gradient) and to markers of cardiac dysfunction (QT interval, heart rate, plasma volume) but not to indicators of the hyperdynamic circulation. Moreover, in multiple regression analysis, proBNP and BNP were also related to arterial carbon dioxide and oxygen tensions. The rate of hepatic disposal of proBNP and BNP was not significantly different in cirrhotic patients and controls. Conclusion: Elevated circulating levels of proBNP and BNP in patients with cirrhosis most likely reflects increased cardiac ventricular generation of these peptides and thus indicates the presence of cardiac dysfunction, rather than being caused by the hyperdynamic circulatory changes found in these patients.